2017
DOI: 10.1111/1471-0307.12397
|View full text |Cite
|
Sign up to set email alerts
|

Soya bean oil/soya protein isolate and carrageenan emulsions as fat replacer in fat‐reduced Oaxaca‐type cheese

Abstract: Milk fat was replaced in Oaxaca‐type cheese with soya bean oil emulsions stabilised with soya protein isolate and different carrageenans (kappa, iota and lambda). Inclusion of soya bean oil emulsion increased yield, moisture and protein content and reduced fat content. Fat reduction and moisture incorporation provoked a tougher but less ductile texture. Specific interaction of carrageenans with milk proteins resulted in larger spreading area when melted and a softer and more adhesive texture, particularly in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 26 publications
(51 reference statements)
0
10
1
Order By: Relevance
“…All these results differ from those of Totosaus et al. (2017), in which, as per observation, they reported an increase of the meltability of a pasta filata Oaxaca type cheese with 25%, 50%, and 75% replacement of milk fat by soybean oil. This result was related to the change in the moisture content of cheese analogues by increasing or decreasing the inclusion of vegetable oil which was not reported in the studies already described.…”
Section: Importance Of Fat Replacement In Cheese Analoguescontrasting
confidence: 95%
See 3 more Smart Citations
“…All these results differ from those of Totosaus et al. (2017), in which, as per observation, they reported an increase of the meltability of a pasta filata Oaxaca type cheese with 25%, 50%, and 75% replacement of milk fat by soybean oil. This result was related to the change in the moisture content of cheese analogues by increasing or decreasing the inclusion of vegetable oil which was not reported in the studies already described.…”
Section: Importance Of Fat Replacement In Cheese Analoguescontrasting
confidence: 95%
“…Regarding meltability, most studies show that when milk fat is replaced by vegetable fat, there is a tendency to a decreased meltability (Cunha et al., 2013; Leong et al., 2020; Ramel & Marangoni, 2018). On the contrary, one of the studies reported an increase in meltability after milk fat replacement (Totosaus et al., 2017). Considering the results presented above, one must take into account how the total or partial substitution of milk fat by vegetable oils can affect the rheological characteristics of cheeses to develop analogues that conserve traditional technological properties.…”
Section: Importance Of Fat Replacement In Cheese Analoguesmentioning
confidence: 96%
See 2 more Smart Citations
“…However, to increase the oil retention, the inclusion of surfactants agents such as soy protein has been studied. Totosaus et al (2017), incorporated an emulsion of soybean oil, soy protein, and different types of carrageenan in an Oaxaca-type cheese (white and soft cheese of Mexican origin). The authors found a higher moisture and protein content and a lower fat content with a milk fat replacement greater than 75%.…”
Section: Cheese Fortification By Direct Incorporation Of Oils and Oilmentioning
confidence: 99%